Nitrided zero-valent iron material with core-shell structure prepared by gas-phase thermochemical synthesis as well as preparation method and application of nitrided zero-valent iron material

The preparation of core-shell structure zero-valent iron nitride material through gas-phase thermal chemical synthesis has solved the safety hazards, high energy consumption and low activity in the preparation method of nano-nitride iron materials in the prior art, and achieved high efficiency Effects of removing chlorinated hydrocarbon organic pollutants.

CN119461622APending Publication Date: 2025-02-18QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES) +1

Patent Information

Application Number
CN202411596925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing preparation methods for nitride nano zero-valent iron materials have problems such as safety hazards, high energy consumption and low activity, and it is difficult to effectively remove chlorinated hydrocarbon organic pollutants.

Method used

The core-shell structure zero-valent iron material was prepared by gas-phase thermal chemical synthesis. By calcining iron powder and melamine in quartz tubes, the reaction of melamine release ammonia gas and zero-valent iron to form a Fe4.4N shell to form a stable iron nitrogen Compound layer.

Benefits of technology

The obtained core-shell structure zero-valent iron nitride surface layer is more stable, has higher electronic efficiency, can effectively remove chlorinated hydrocarbon organic pollutants, and the preparation method is simple to operate and short cycle, which is suitable for practical engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461622A_ABST
    Figure CN119461622A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental restoration, in particular to a core-shell structure nitrided zero-valent iron material obtained through gas-phase thermochemical synthesis as well as a preparation method and application of the core-shell structure nitrided zero-valent iron material. The invention provides a core-shell structure nitrided zero-valent iron material prepared through gas-phase thermochemical synthesis. The core of the core-shell structure nitrided zero-valent iron material is zero-valent iron, and the shell of the core-shell structure nitrided zero-valent iron material is Fe4.4N; the content of zero-valent iron is 60-70wt% based on the mass of the nitrided zero-valent iron material with the core-shell structure. According to the core-shell structure nitrided nano zero-valent iron material obtained through gas-phase chemical thermal synthesis, zero-valent iron is used as a core, and Fe4.4N is used as a shell; the obtained core-shell nitrided nano zero-valent iron material has a more stable surface iron-nitrogen compound, has higher electronic efficiency, and can overcome the problem of rapid passivation of nano zero-valent iron in the repair process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental remediation, and in particular to a gas phase thermochemically synthesized core-shell structured zero-valent iron nitride material and a preparation method and application thereof. Background Art

[0002] Zero valent iron (Fe 0 ) is abundant in source and cheap in price, because it has strong reducing property (Fe 2+ +2e - →Fe(s), E0=-0.44V) and adsorption are widely used in environmental pollution control. In-situ groundwater remediation technology based on zero-valent iron has received widespread attention at home and abroad. However, zero-valent iron easily reacts with water to passivate and form an iron oxide protective layer. When zero-valent iron removes pollutants in groundwater, it first loses electrons and is oxidized. Part of the electrons given are used to remove pollutants, and part is obtained by protons H in water to generate non-toxic, colorless, and odorless hydrogen (Hydrogen, H2). The production of H2 reduces the efficiency of zero-valent iron in removing pollutants to a certain extent. At the same time, nano zero-valent iron is easy to aggregate into large particles due to its magnetism and high surface energy and loses its underground fluidity; it has high activity but short lifespan and cannot continuously degrade pollutants; the dense oxide film formed on the surface of zero-valent iron greatly hinders the contact between active ingredients and target pollutants, thereby reducing the activity of zero-valent iron.

[0003] In recent years, a large number of studies have shown that doping with heteroatoms of different electronegativity (e.g., S, C, N, or P) is an effective way to readjust the distribution of delocalized electrons around the d orbital of Fe atoms. In the past few decades, iron nitride has been used in various scientific research fields as a highly corrosion-resistant material and electrochemical catalyst. Since N has a higher electronegativity and a more significant electron shuttling effect than S, nitridation of the zero-valent iron surface has gradually become a new method for modifying zero-valent iron. Studies have shown that nitriding the surface of zero-valent iron can give it the following advantages: (1) An iron-nitrogen compound layer can be formed on the surface of zero-valent iron to replace the original oxide layer. Compared with the iron oxide layer on the original zero-valent iron surface, the iron-nitrogen compound has excellent electronic conductivity, which can facilitate the transfer of electrons given by the zero-valent iron core, thus overcoming the disadvantage of low activity of zero-valent iron; (2) The iron-nitrogen compound also has good hydrophobicity, which is conducive to the adhesion of chlorinated hydrocarbon oily organic matter, thereby promoting the contact between pollutants and their active sites. The electrons given by the zero-valent iron core are also more easily transferred to the target pollutants through the iron-nitrogen compound layer, thereby degrading the target pollutants; (3) The nitrogen element in the iron-nitrogen compound can inhibit the H3O + Get electrons and then form hydrogen, which greatly inhibits the H3O + Compete with target pollutants for electrons and improve the electronic efficiency of zero-valent iron.

[0004] At present, the existing method for preparing nitride nano zero-valent iron is mainly the thermochemical ammonia synthesis method (Brumovsky M, Oborna J, Micic V, et al. Iron Nitride Nanoparticles for Enhanced Reductive Dechlorination of Trichloroethylene [J]. Environ Sci Technol, 2022, 56 (7): 4425-4436.). The configuration of iron nitride is Fe 2-3 N and Fe4N; and ball milling method (Gong L, Qiu X, Tratnyek PG, et al. FeN(x)(C)-Coated Microscale Zero-Valent Iron for Fast and Stable Trichloroethylene Dechlorination in both Acidic and Basic pH Conditions[J]. Environ Sci Technol, 2021, 55(8): 5393-5402.) The chemical forms of nitrogen are pyridine nitrogen, pyrrole nitrogen and graphene nitrogen. However, there are the following shortcomings: (1) The current gas phase thermochemical synthesis method uses ammonia for synthesis, which is not easy to store and transport, is toxic, and is prone to explosion, posing a safety hazard; (2) The ball milling synthesis method has high energy consumption and is difficult to reach the nanoscale, which affects the degradation rate; (3) The configuration of iron nitride is Fe 2-3 N and Fe4N as well as the single chemical forms of pyridinic nitrogen, pyrrolic nitrogen and graphene nitrogen have low activity in modified zero-valent iron.

[0005] Therefore, based on the current research status, it is necessary to explore new preparation methods for nitrided zero-valent iron to solve the above technical problems. Summary of the invention

[0006] The present invention provides a core-shell structured zero-valent iron nitride material synthesized by gas phase thermochemical synthesis and a preparation method and application thereof. The core of the obtained core-shell structured zero-valent iron nitride material is zero-valent iron and the shell is Fe 4.4 N is less susceptible to oxidation than existing nitrided zero-valent iron materials, and the prepared nitrided zero-valent iron has a higher removal efficiency for chlorinated hydrocarbon organic pollutants. At the same time, the gas phase thermochemical synthesis method provided by the present invention is simple to operate, has a short preparation cycle, and is more likely to meet the application of practical engineering.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a core-shell structured zero-valent iron nitride material synthesized by gas phase thermochemical synthesis, wherein the core of the core-shell structured zero-valent iron nitride material is zero-valent iron and the shell is Fe 4.4 N; based on the mass of the core-shell structured nitrided zero-valent iron material, the zero-valent iron content is 60-70wt%.

[0009] The present invention also provides a method for preparing a core-shell structured nitrided zero-valent iron material by gas phase thermochemical synthesis, comprising: placing iron powder and melamine in a quartz tube with a partition plate, wherein the partition plate divides the quartz tube into a space for holding the iron powder and a space for holding the melamine, wherein the space for holding the iron powder and the space for holding the melamine are interconnected; vacuum sealing the quartz tube, and then calcining the quartz tube containing the iron powder and melamine at above 350° C. to obtain a core-shell structured nitrided zero-valent iron material.

[0010] Melamine will decompose and release ammonia at a temperature slightly higher than 350°C (ammonia is the only gaseous product of melamine decomposition). Ammonia can react with the oxide layer (Fe x O y ) or part of the Fe near the outer layer 0 The reaction generates an iron-nitrogen compound layer, which then replaces the surface oxide of the zero-valent iron particles. The superior conductivity of iron nitride can accelerate the rate at which the inner core zero-valent iron transfers electrons to the target pollutant. In addition, iron nitride has good hydrophobicity and has a strong affinity for hydrophobic pollutants such as chlorinated hydrocarbons, thereby improving its performance in degrading target pollutants. On the other hand, the presence of iron nitride can inhibit the hydrogen evolution reaction between the zero-valent iron material and water molecules, weaken the competition between water molecules and pollutants for electrons, and thus increase the electronic efficiency of zero-valent iron.

[0011] Preferably, the mass ratio of the melamine to the iron powder is 0.5 to 3:1.

[0012] More preferably, the mass ratio of the melamine to the iron powder is 1 to 3:1.

[0013] Further preferably, the mass ratio of the melamine to the iron powder is 1 to 2:1.

[0014] More preferably, the mass ratio of the melamine to the iron powder is 1 to 1.5:1.

[0015] Preferably, the particle size of the iron powder is 50-800 nm.

[0016] Under this condition, the relative content of zero-valent iron in the generated zero-valent iron nitride is appropriate, and the zero-valent iron nitride has a better removal effect on chlorinated hydrocarbon organic pollutants.

[0017] More preferably, the particle size of the iron powder is 100-500 nm.

[0018] More preferably, the particle size of the iron powder is 100-300 nm.

[0019] More preferably, the particle size of the iron powder is 100 nm.

[0020] Preferably, one end of the partition plate is connected to the quartz tube, and the length of the partition plate is 1 / 5 to 1 / 2 of the inner diameter of the quartz tube.

[0021] Preferably, after vacuum sealing, the vacuum degree in the quartz tube is ≥0.1 Mpa.

[0022] Preferably, the calcination is specifically: calcination at 350-400° C. for 20-30 min, and then calcination at 400-600° C. for 60-120 min.

[0023] More preferably, the calcination is specifically: calcination at 350-360° C. for 20-30 min and then calcination at 500-600° C. for 80-120 min.

[0024] Preferably, the heating rate to 350-400° C. is 1-5° C. / min; the heating rate to 400-600° C. is 2-3° C. / min.

[0025] More preferably, the heating rate to 350-360° C. is 1-3° C. / min; the heating rate to 500-600° C. is 2° C. / min.

[0026] When the iron nitride layer in the core-shell structured zero-valent iron nitride material is too thick, although the electron efficiency of the zero-valent iron nitride can be close to 100%, the relative content of zero-valent iron inside the material particles will be reduced. The zero-valent iron inside the particles is the only electron donor for degrading pollutants, and too low a content of zero-valent iron will affect its reaction activity.

[0027] Therefore, in the parameter setting of the nitriding process: calcination temperature, calcination time, heating rate, particle size of iron powder particles, and the ratio of melamine to iron powder will all affect the thickness of the iron nitride layer. For example: calcination time is too long, heating rate is too fast, iron powder particle size is too small, and the ratio of melamine to iron powder is too high, which will lead to excessive degree of nitridation, thereby affecting the degradation rate.

[0028] The present invention also provides the use of the core-shell structure nitrided zero-valent iron material or the core-shell structure nitrided zero-valent iron material prepared by the above preparation method in in-situ remediation of groundwater containing chlorinated hydrocarbon organic pollutants.

[0029] Preferably, the chlorinated hydrocarbon organic pollutants are one or more of trichloroethylene, tetrachloroethylene, trichloroethane, tetrachloroethane, chloromethane, dichloromethane, chloroform, carbon tetrachloride, trichloropropane, and hexachlorobutadiene.

[0030] Therefore, the present invention has the following beneficial effects:

[0031] (1) The present invention uses a core-shell structured nitrided nano zero-valent iron material obtained by gas phase chemical thermal synthesis, with a zero-valent iron core and Fe 4.4 N is the outer shell; the obtained core-shell structured nitrided nano zero-valent iron material has a more stable surface iron-nitrogen compound, higher electronic efficiency, and can overcome the problem of rapid passivation of nano zero-valent iron during the repair process.

[0032] (2) The present invention utilizes ammonia generated during the calcination of melamine as the synthesis introduction gas, thereby avoiding the drawbacks of the existing gas phase synthesis method that ammonia is difficult to transport and store and is prone to explosion.

[0033] (3) The gas-phase thermochemical synthesis method provided by the present invention is easy to operate, has a short preparation cycle, and is more easily applicable to practical engineering applications.

[0034] (4) The core-shell nitrided nano zero-valent iron material obtained by the present invention has a high removal efficiency for chlorine-containing organic pollutants, and can reduce and convert chlorine-containing organic pollutants into pollution-free ethane, acetylene, ethylene, etc., and is suitable for in-situ remediation of groundwater. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the structure of a sealed quartz tube;

[0036] Figure 2 Schematic diagram of the experiment of the sealed quartz tube in Example 1;

[0037] Figure 3 Transmission electron microscope (TEM) images of gas phase chemical thermal synthesis nitrided nano zero-valent iron prepared in Example 1, wherein A is a TEM morphology image, B is a ring high angle dark field image (HADDF) comprehensive element (nitrogen, oxygen, iron) distribution map, C is a HADDF line scan nitrogen, oxygen, and iron element content distribution map, D is a HADDF oxygen element distribution map, E is a HADDF iron element distribution map, and F is a HADDF nitrogen element distribution map;

[0038] Figure 4 XRD diagram of gas phase chemical thermal synthesis nitrided nano zero-valent iron prepared in Example 1;

[0039] Figure 5 The XPS graph of the vapor phase chemical thermal synthesis nitrided nano zero-valent iron prepared in Example 1, wherein a is the full spectrum of XPS, and b is the partial range spectrum of XPS;

[0040] Marked in the figure: 100 quartz tube; 200 partition board. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0042] The zero-valent iron powder and melamine in this part were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0043] Example 1

[0044] Prepare a Figure 1 The quartz tube 100 shown in the figure has a partition plate 200 disposed inside the quartz tube 100 with one end connected to the quartz tube 100, and the length of the partition plate 200 is 1 / 2 of the inner diameter of the quartz tube 100; the following experiment is then carried out.

[0045] like Figure 2 As shown, 5g (particle size 100nm) of zero-valent iron powder and 5g of melamine are placed on both sides of the quartz tube 100, and then the quartz tube 100 is vacuum-sealed by hot-melt sealing with a vacuum degree of 0.1MPa. After hot-melt sealing, the quartz tube 100 is placed in a muffle furnace. Heating I: Heating to 360°C at a heating rate of 2°C / min and maintaining for 30min; Heating II: Heating to 480°C at a heating rate of 1°C / min and maintaining for 100min. During the heating process, when the temperature is slightly higher than 350°C, melamine is thermally decomposed to release ammonia, and the pressure inside the quartz tube 100 also increases. Under high temperature and high pressure conditions, ammonia reacts with the iron oxides on the surface of the iron powder particles and the Fe near the surface. 0 Reaction to generate Fe 4.4 N, after the calcination is completed and the quartz tube 100 is opened after cooling to room temperature, a nitrided nano zero-valent iron composite material with a core-shell structure can be obtained.

[0046] The nitrided nano zero-valent iron material prepared in this embodiment was characterized, and the results are as follows: Figure 3 , 4 and 5; Figure 3 This is a transmission electron microscope photo of the nitrided nano-zero-valent iron prepared in Example 1. It can be clearly seen that there is nitrogen in the material. The results show that the nitrided nano-zero-valent iron prepared by the vapor phase thermal synthesis method has a typical core-shell structure, with a core of zero-valent iron and an outer shell of iron-nitrogen compound. Figure 4 The XRD spectrum shows that the nitrided form of iron is Fe 4.4 N, different from other nitrided zero-valent iron materials obtained by gas phase synthesis or ball milling; Figure 5 The XPS graph shows that Fe xN, nitrogen and iron are coordinated to form iron nitride, which is the nitrided nano zero-valent iron material required by the present application. Figure 3 , Figure 4 , Figure 5 It can be concluded that melamine can decompose under high temperature conditions to form NH3 and react with zero-valent iron, and form iron-nitrogen compounds on the particle surface, and finally prepare core-shell structure nitrided nano zero-valent iron. Based on the mass of nitrided nano zero-valent iron material, the mass percentage of zero-valent iron is 65%, and the mass percentage of iron-nitrogen compounds is 31%.

[0047] Examples 2 to 20 and Comparative Examples 1 to 9 were prepared in the same manner as Example 1 under the conditions in Table 1 to obtain nitrided nano-zero-valent iron with a core-shell structure.

[0048] Table 1 Conditions of each embodiment / comparative example

[0049]

[0050]

[0051] Note: N / Fe 0 is the mass ratio of melamine to iron powder

[0052]

Performance test

[0053] Taking trichloroethylene (or tetrachloroethylene, trichloroethane, tetrachloroethane, trichloropropane, methyl chloride, dichloromethane, chloroform) as the target pollutant, the activity of the nitrided nano zero-valent iron composite materials prepared in Examples 1 to 20 and Comparative Examples 1 to 9 was investigated.

[0054] The specific implementation steps are as follows: 0.025g of the nitrided nano zero-valent iron material obtained in Example 1 (or any one of Examples 1 to 20 and Comparative Examples 1 to 9) is added to a 50mL reaction bottle, and then 25mL of deoxygenated pH buffer solution (50mM HEPES, pH=7.0) is added. At this time, the mass concentration of the nitrided nano zero-valent iron is 1g / L, and then an appropriate amount of trichloroethylene stock solution is injected to ensure that the initial concentration of trichloroethylene is 10mg / L, and the experiment is carried out. The concentration of trichloroethylene (or tetrachloroethylene, trichloroethane, tetrachloroethane, trichloropropane, monochloromethane, dichloromethane, trichloromethane) is monitored in real time by gas chromatography, and the results are shown in Table 2.

[0055] Table 2 Degradation performance of organic pollutants

[0056]

[0057]

[0058] From Table 2, it can be seen that the core-shell structured nitrided nano zero-valent iron prepared in the present application shows a removal rate of more than 95% for various chlorinated hydrocarbon organic pollutants such as trichloroethylene, tetrachloroethylene, trichloroethane, tetrachloroethane, trichloropropane, monochloromethane, dichloromethane, and chloroform.

Claims

1. A core-shell structured zero-valent iron nitride material synthesized by gas phase thermochemical synthesis, characterized in that: The core of the core-shell structured nitrided zero-valent iron material is zero-valent iron, and the shell is Fe 4.4 N; based on the mass of the core-shell structured nitrided zero-valent iron material, the zero-valent iron content is 60-70wt%.

2. The method for preparing the core-shell structured zero-valent iron nitride material by gas phase thermochemical synthesis as claimed in claim 1, characterized in that: include: The iron powder and melamine are placed in a quartz tube with a partition plate, wherein the partition plate divides the quartz tube into a space for holding the iron powder and a space for holding the melamine, and the space for holding the iron powder and the space for holding the melamine are interconnected; the quartz tube is vacuum-sealed, and then the quartz tube containing the iron powder and melamine is calcined at above 350° C. to obtain a core-shell structured nitrided zero-valent iron material.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the melamine to the iron powder is 0.5 to 3:

1.

4. The preparation method according to claim 2 or 3, characterized in that: The particle size of the iron powder is 50 to 800 nm.

5. The preparation method according to claim 2, characterized in that: One end of the partition plate is connected to the quartz tube, and the length of the partition plate is 1 / 5 to 1 / 2 of the inner diameter of the quartz tube.

6. The preparation method according to claim 2 or 5, characterized in that: After vacuum sealing, the vacuum degree in the quartz tube is ≥0.1Mpa.

7. The preparation method according to claim 2, characterized in that: The calcination is specifically: calcination at 350-400° C. for 20-30 min, and then calcination at 400-600° C. for 60-120 min.

8. The preparation method according to claim 2 or 7, characterized in that: The heating rate to 350-400°C is 1-5°C / min; the heating rate to 400-600°C is 2-3°C / min.

9. Use of the core-shell structured nitrided zero-valent iron material as claimed in claim 1 or the core-shell structured nitrided zero-valent iron material prepared by the preparation method as claimed in any one of claims 2 to 8 in in-situ remediation of groundwater containing chlorinated hydrocarbon organic pollutants.

10. The use according to claim 9, characterized in that The chlorinated hydrocarbon organic pollutants are one or more of trichloroethylene, tetrachloroethylene, trichloroethane, tetrachloroethane, methyl chloride, dichloromethane, chloroform, carbon tetrachloride, trichloropropane, and hexachlorobutadiene.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-doped zero-valent iron composite material

    CN111847541A

  • Oxygen reduced iron-tetrairon nitride@ monatomic iron and nitrogen co-doped amorphous carbon-carbon black composite catalyst, and preparation and application thereof

    CN113054210A

  • Phosphorized zero-valent iron material with core-shell structure as well as preparation method and application of phosphatized zero-valent iron material

    CN116351445A

  • Regenerable solvent mixtures for acid-gas separation

    US20170252695A1

Cited By

  • Magnetically-driven self-diffusion zero-valent iron-based composite material as well as preparation method and application thereof

    CN122502001A